2014
DOI: 10.1111/eff.12136
|View full text |Cite
|
Sign up to set email alerts
|

Prey C:P ratio and phosphorus recycling by a planktivorous fish: advantages of fish selection towards pelagic cladocerans

Abstract: Prey selection by the small planktivore Galaxias maculatus and phosphorus gain depending on diet has been examined related to predator–prey daily distribution. Prey elemental composition (C:P ratio) was analysed as a factor of selectivity. Field experiments were carried out to evaluate the effect of prey on phosphorus recycling. Results revealed that the pelagic cladoceran Ceriodaphnia dubia was a highly selected prey by all fish sizes at dawn and dusk, despite its low abundances in comparison with other zoopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 50 publications
0
11
0
1
Order By: Relevance
“…Meanwhile, adults also reflect a high consumption of pelagic prey enriched in 15 N relative to insect larvae and closer to P3. In this sense, Reissig et al (2015) observed a high selection of small puyen towards pelagic prey for all fish sizes during night in the neighboring Lake Moreno. These authors demonstrated that juveniles and adults of small puyen use low light "windows" as refuge from large visual predators as P. trucha and introduced salmonids to exploit high quality pelagic resources.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…Meanwhile, adults also reflect a high consumption of pelagic prey enriched in 15 N relative to insect larvae and closer to P3. In this sense, Reissig et al (2015) observed a high selection of small puyen towards pelagic prey for all fish sizes during night in the neighboring Lake Moreno. These authors demonstrated that juveniles and adults of small puyen use low light "windows" as refuge from large visual predators as P. trucha and introduced salmonids to exploit high quality pelagic resources.…”
Section: Discussionmentioning
confidence: 83%
“…Due to their high mobility, fish function as a strong link between bentho-littoral and pelagic habitats by feeding on prey from both habitats (Schindler and Scheuerell, 2002;Vander Zanden and Vadeboncoeur, 2002;Barriga et al, 2012;Reissig et al, 2015). In Patagonian lakes, exotic salmonids, particularly rainbow trout, play a major role in habitat coupling through predation in both bentho-littoral and pelagic habitats (Juncos et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In unpolluted conditions the calanoids copepods would have an important role as grazer on phytoplankton and in turn would be eaten by zooplanktivorous fishes in Argentinean and Chilean Patagonian lakes (Soto and Zuñiga, 1991;De los Rios-Escalante, 2010;Reissig et al, 2015;Trochine et al, 2015). Additionally, the natural ultraviolet radiation exposure that increased in Patagonia affect zooplankton assemblages because the species have different tolerance to UV radiation under trophic gradient (Marinone et al, 2006;De los Ríos-Escalante, 2010;Hylander et al, 2012).…”
Section: Discussionmentioning
confidence: 99%